Game Risk Management Methods for Investment Portfolio Optimization - Балджи, Марина Дмитрівна; Baldzhy, Maryna D.; Iryna, Bashynska; Larysa, Ivanchenkova; Larysa, Skliar; Olena, Nikoliuk; Galina, Tkachuk (My University, 2019)
The world is on the verge of technological revolution, which will fundamentally change the way of life, work and attitude towards each other [1]. We live in the era of the Third Industrial (or Digital) Revolution, but modern world leaders are already actively preparing for a new period - the Fourth Industrial Revolution or Industry 4.0. New forms of interaction open up opportunities in the organization of work and change requirements for employees. Business becomes digital, but the person stays. Employees will continue to remain crucial factors in innovation, continually developing products and services. The lack of talented and skilled personnel will be the main problem of the Fourth Industrial Revolution. Flexible production through FIR will require much more skills in all workflows for all employees. Skilled workers will be more in demand in the future for making decisions that can not be replaced by any algorithm. At the same time, employees must be trained and qualified for new jobs, so it is essential to review standards, for example, in education and training, and adapt them to new requirements. The implementation of interactive technologies in learning has become a necessity. One of the effective methods is business games: both independently and in combination with theoretical training. Precisely this combination (practice) is optimal for students to learn lecture material and acquire competencies. The article is devoted to the description of the technique of conducting risk management training. We described the technology of the training, dividing it into two parts. In the first part, the students are reminded of the risk management theory; in the second part, a business game is held - "Investment portfolio". In the article, we showed how it could be carried out with and without the use of gadgets/computers. As an example, we considered the most frequent mistake when conducting this game and gave a correct model. Besides, in
Game Risk Management Methods for Investment Portfolio Optimization / I. Bashynska, M. Baldzhy, L. Ivanchenkova, L. Skliar, O. Nikoliuk, G. Tkachuk // International Journal of Recent Technology and Engineering. – 2019. – Vol. 8, Issue-2. – Р. 3940-3943. DOI: 10.35940/ijrte.B1729.078219
Keywords: risk; probability; profitability; risk management; Research Subject Categories::SOCIAL SCIENCES